Minutes of the 7th Meeting of BRAC University Academic Council (AC) - Academic Council, BRAC University (Vice Chancellor's Office, BRAC University, 2013)
Minutes of the 7th Meeting of BRAC University Academic Council, held on Monday, 13th March, 2003